Pilihan Bahasa pada Caption Akun X Ganjar Pranowo - Nabilla Maulida Fitria; Hari Bakti Mardikantoro (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
Language as a tool of communication plays a vital role in facilitating human interaction. One of the academic disciplines used to study language is sociolinguistics, which examines the relationship between language and society. Language choice is one of the issues examined in sociolinguistics. This study aims to examine language choice in the captions of Ganjar Pranowo’s X account and the factors that influence it. The research employed a qualitative descriptive method, using observation, note-taking, and documentation as data collection techniques. The data were analyzed using the agih and padan methods. The results indicate the presence of various forms of language choice in the captions of Ganjar Pranowo’s X account. Language choice is influenced by the conversation partner, the topic of conversation, and the context, including time and place. This study contributes to enriching sociolinguistic knowledge, particularly in the study of language choice in social media communication. It is expected to contribute to the field of linguistics and serve as a reference for future research on language choice and social media discourse, especially in contemporary social media and public communication contexts.